The Role of Brain Natriuretic Peptide in the Prediction of Cardiac Performance in Coronary Artery Bypass Grafting - Saribulbul, Osman (2003)
The relationship between brain natriuretic peptide and cardiopulmonary bypass has not been examined sufficiently. In this study, we prospectively examined brain natriuretic peptide levels in the plasma of 26 patients undergoing coronary artery bypass grafting. Brain natriuretic peptide measurements were carried out at 4 times: preoperatively, 3 hours after institution of cross-clamping, 24 hours after institution of cross-clamping, and on the 5th postoperative day. In addition, we measured individual variables and compared them to brain natriuretic peptide levels. Mean preoperative brain natriuretic peptide levels were significantly higher in patients with histories of myocardial infarction (P = 0.0047) and heart failure (ejection fraction ≤0.40) (P = 0.0001). There was a significant correlation between preoperative brain natriuretic peptide levels and cross-clamp times (P = 0.028), and an inverse correlation between those levels and preoperative cardiac indices (P = 0.001). The preoperative brain natriuretic peptide level also correlated inversely with left ventricular ejection fraction before (P = 0.001) and 5 days after (P = 0.01) operation. When the Clinical Severity Scoring System was applied, preoperative brain natriuretic peptide plasma concentrations in 19 patients with risk scores of 0–2 were significantly lower than in the 7 patients whose risk scores were 3–6 (P = 0.006). There was also a significant relationship between preoperative brain natriuretic peptide plasma concentrations and the postoperative requirement for inotropic agents (P = 0.027). This study suggests that plasma brain natriuretic peptide concentration could be one of the predictors of risk in patients undergoing coronary artery bypass grafting. (Tex Heart Inst J 2003;30:298–304)